Telaah Dampak Kebijakan Impor terhadap Industri Tekstil Nasional: Idealitas Perlindungan Ekonomi Domestik: indonesia - Kharim Aliansyah, Dizma; Aurelia Tyasari, Helga; Maharani Putri, Karina (Forschungsforum Law Journal, 2025)
The national textile industry, contributing US$33 billion annually and millions of jobs, faces challenges due to import policies, particularly the Minister of Trade Regulation (Permendag) Number 8 of 2024. Intended to streamline goods flow, this policy has instead driven a 5.84% increase in textile imports in 2024, triggering negative growth in the textile sector and mass layoffs. The literature review draws on Richard Posner’s law and economics theory, emphasizing regulatory efficiency, and examines import policies in India, Vietnam, and Turkey for best practices. This study employs a normative legal method with statutory, conceptual, and comparative approaches, analyzing primary and secondary data using descriptive and evaluative techniques based on the IRAC method. The discussion reveals that relaxed import rules have allowed cheap and illegal products to flood the market, undermining local industry competitiveness, compounded by complex permitting bureaucracy and poor inter-agency coordination. The conclusion underscores the need for balanced policy reform to protect domestic industries while supporting supply chains, through digitalized permitting, innovation incentives, and stringent oversight. The study recommends regulatory harmonization and learning from other countries to enhance Indonesia’s textile competitiveness globally.